6th ICBSTA - Proceeding of selected articles - Faculty of Science (AlQalam Journal of Medical and Applied Sciences, 2024)
Sixth International Conference of Basic Sciences and Their Applications (6th ICBSTA) is an event hosted by Elbeida City in Faculty of science - Omar AlMukhtar University. This conference aims to exchange scientific experiences and suggestions to solve various problems facing our country in the fields of basic sciences, The conference is an excellent opportunity to learn about the latest scientific research in various basic sciences and applications.